Study on demographic factors of discharge against medical advice in pediatric population - U., Vidya B.; K., Anil Shetty (International Journal of Contemporary Pediatrics, 2020)
Background: Discharge against medical advice (DAMA) is of serious concern among the pediatrics population. Parent(s)/guardians understanding about the disease and various other factors play role in their decision of DAMA. The aim of this study is to know the prevalence of DAMA in a tertiary care center and to observe the gender stratification in DAMA. Methods: A retrospective survey of medical records of children discharge against medical advice during the period January 2017 to January 2019. Demographic data, length of hospital stay, clinical diagnosis and procedure refused was collected. Results: Total 12977 were discharged during the study period of which, 387 children were DAMA, prevalence of DAMA was 2.9%, male to female ratio among DAMA patients is 1.2:1. The mean length of stay was 4.8 days. Among the DAMA patients’ newborns were predominant (61.6 %), p value = 0.0001, highly significant. No significant difference with respect to age and gender (p value = 0.535). Out of 370 DAMA patients, 211 patients who required further investigations and procedure was refused by parents/guardians (p value = 0.0001) highly significant. Phototherapy refusal was most common among newborn (59.7%), followed by neuroimaging and lumbar puncture in children (10.9%). Conclusions: DAMA was observed more among the newborns compared to infants, toddlers and children. Among newborns, phototherapy refusal was most common. In infants and children neuroimaging and lumbar puncture was the most commonly refused procedure. There was no gender bias.